Retrograde femoral nails for emergency stabilization in multiply injured patients with haemodynamic instability. (October 2020) - Al Maskari, Sultan; Muzaffar, Rahil; Yaseen, Ahmed
Abstract: Introduction: The purpose of this study is to retrospectively evaluate the immediate effect of retrograde intramedullary femoral nail (RIMFN) fixation technique on patient's hemodynamic status as documented by vital signs (blood pressure and pulse) intraoperatively in all patients with femoral shaft fractures with multiple injuries and hemodynamic instability who were treated with RIMFN at our institution on emergency basis as part of damage control orthopaedics. Patients and methods: A retrospective review of intra operative vital signs obtained from patient records was completed at a Level 1 trauma center in a university hospital. In all, 11 multiply injured patients with (14) femur fractures with hemodynamic instability were identified. Of those, 3 had bilateral femur fractures. Closed reduction and retrograde femoral nailing without proximal locking was performed to achieve immediate skeletal and haemodynamic stability. Pulse rate and BP measurements were noted for all patients starting from the time patient would enter the operating room till the patient was shifted back to the recovery ward. Results: The average cohort age was 28 years (20–36 years). The average Injury Severity Score was 28 (16–50). Statistically significant improvement in pulse rate and blood pressure was noted following femoral fracture fixation with intramedullary nail. No cases of infection or symptomatic fat or pulmonary embolism were encountered. One patient required exchange nailing for non-union and one femur underwent later lengthening. Conclusions: Retrograde Intramedullary femoral nail can be an effective alternative to external fixator as damage control device and is associated with immediate improvement in vital signs (pulse and blood pressure) intra operatively. Highlights: Reversal of shock is important determinant of outcome in multiply injured patients. Retrograde femoral nailing achieves immediate haemodynamic stability. Retrograde nailing as damage control device has low morbidity and mortality. Retrograde nailing without proximal locking is rapid, safe, effective procedure.